Evaluación de la adición de cereales sin gluten como adjunto del trigo y cebada en la elaboración de una cerveza artesanal tipo Ale. (2023)
In the present project, the physicochemical, sensory and microbiological properties of an Amber American Ale style craft beer using malt from a gluten-free cereal as an adjunct are evaluated. Initially, the characteristics of gluten-free cereals are exposed in order to choose the most optimal option for the production of Ale-type beer. The necessary stages for the malting process of the chosen cereal, which is purple corn (Zea Mays), are presented. Likewise, the operating conditions for the production of beer are established taking into account the quality parameters established for the style of beer.